Organization practice - O'Connor, Mary Katherine (Wiley, 2009)
Rev. edition of: Organization practice / F. Ellen Netting, Mary Katherine O'Connor; Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)